Pathway and regulation of erythritol formation in Leuconostoc oenos. - Veiga-da-Cunha, M (1993)
It was recently observed that Leuconostoc oenos GM, a wine lactic acid bacterium, produced erythritol anaerobically from glucose but not from fructose or ribose and that this production was almost absent in the presence of O2. In this study, the pathway of formation of erythritol from glucose in L. oenos was shown to involve the isomerization of glucose 6-phosphate to fructose 6-phosphate by a phosphoglucose isomerase, the cleavage of fructose 6-phosphate by a phosphoketolase, the reduction of erythrose 4-phosphate by an erythritol 4-phosphate dehydrogenase and, finally, the hydrolysis of erythritol 4-phosphate to erythritol by a phosphatase. Fructose 6-phosphate phosphoketolase was copurified with xylulose 5-phosphate phosphoketolase, and the activity of the latter was competitively inhibited by fructose 6-phosphate, with a Ki of 26 mM, corresponding to the Km of fructose 6-phosphate phosphoketolase (22 mM). These results suggest that the two phosphoketolase activities are borne by a single enzyme. Extracts of L. oenos were also found to contain NAD(P)H oxidase, which must be largely responsible for the reoxidation of NADPH and NADH in cells incubated in the presence of O2. In cells incubated with glucose, the concentrations of glucose 6-phosphate and of fructose 6-phosphate were higher in the absence of O2 than in its presence, explaining the stimulation by anaerobiosis of erythritol production. The increase in the hexose 6-phosphate concentration is presumably the result of a functional inhibition of glucose 6-phosphate dehydrogenase because of a reduction in the availability of NADP.